IMPROVING STUDENTS’ WRITING SKILL THROUGH CUE CARD METHOD - Ika Sastrawati (Universitas Muhammadiyah Makassar, 2016)
This research aimed to find the use of Cue Card Method improves the students writing skill at Eight Grade Students of SMP Bajiminasa Makassar. The method of this research was classroom action research consisted of two cycles. One cycle consisted of four meeting. it meant that were eight meetings for two cycles. This classroom action research was done at SMP Bajiminasa Makassar for English subject. As a subject in this research was class VIII.A Junior High School in the 2012-2013 academic year with student’ number as about 36 students’. Those consisted of 26 women and 10 men. the instrument was writing test and observation. The research findings indicated that the application of cue card method was effective and significant in improving the students’ writing skill, especially it focuses on students content and vocabulary. It was proved that the mean score of D-Test was 5.64, Cycle I 6.13 and after conducted Cycle II improved to 8.23 and based two cycle researcher found percentage improvement that is from D-Test to Cycle I is 13.24 % and from Cycle I to II is 29.70 and D-T to Cycle II 46.35 %. Based on the result of the research, it can be concluded that the use of cue card method improves students’ writing skill and class condition. Therefore, it is recommended that the teachers use cue card media in teaching writing.Keywords: Writing Skill, Cue Card Method